Role Of Lockup Provision And Institutional Investors In Restricting Ipo Flipping Activity: Is There A Moderating Effect Of Investor Demand? - Yahya, Norliza Che; Abdul Rahim, Ruzita (Asian Academy of Management (AAM), 2015)
This paper examines the moderating effect of pre-listing investor demand on the direct influence of lockup provision and institutional investors' participation on flipping activity. By definition, flipping activity is a liquidation of IPOs by new shareholders during the first few trading days. If flipping activity is done substantially, it has potential to erode wealth of the issuing companies and shareholders. To reduce such adverse effects, issuers and underwriters could restrict availability of tradable shares in the immediate aftermarket by relying on the direct restrictive role of lockup provision and institutional investors' participation. However, the role of restricting supply of IPOs in the immediate aftermarket could be hindered if the IPOs are highly demanded. The shift of the demand curve to the right when supply of the IPOs is restricted should induce a new equilibrium at a higher price level. The resulting price appreciation will motivate investors to flip to optimize their returns, pushing flipping activity to a higher level. Using data of 370 Malaysian IPOs covering the period from January 2000 to December 2012, this study finds that pre-listing investor demand does moderate the role of lockup provision (period) and institutional investors' participation in restricting flipping activity but in the opposite manner.